ANALISIS PROGRAM PENDIDIKAN VOKASI DALAM MENGHADAPI TANTANGAN INDUSTRI - Riska Angriani; Irjus Indrawan; Alridho Fransiska; Siti Naimah (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2025)
This research aims to analyze the relevance of vocational education programs in Indonesia to the challenges facing industry today. This research uses a descriptive qualitative research type by descriptively explaining qualitative data taken from various articles. The method used is systematic literature review (SLR). The research results show that there is a gap between the skills provided by vocational education institutions and actual needs in the field. For this reason, regular curriculum updates are needed, improving the quality of technology-based teaching, as well as strengthening cooperation between vocational education institutions and industry to create more effective synergies.